Respuestas
Respuesta dada por:
2
Resolver.
2(x - 1) = 5(2x + 3)
2x - 2 = 10x + 15
-2 - 15 = 10x - 2x
- 17 = 8x
-17/8 = x
Respuesta.
x = - 17/8
2(x - 1) = 5(2x + 3)
2x - 2 = 10x + 15
-2 - 15 = 10x - 2x
- 17 = 8x
-17/8 = x
Respuesta.
x = - 17/8
xxguryxx:
gracias es para una prueba de multi chop me sale ese resultado
Respuesta dada por:
0
2 (x - 1) = 5 (2x + 3)
2x - 2 = 10x + 15
2x - 10x = 15 + 2
- 8x = 17
x = -17/8
Solución :
x = -17/8
2x - 2 = 10x + 15
2x - 10x = 15 + 2
- 8x = 17
x = -17/8
Solución :
x = -17/8
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 9 años
hace 10 años